PERAN GURU SEBAGAI IMPLEMENTERS DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN - Siti Aisyah; Mila Nur Aini; Jagad Padang Gemilang; Siti Zazak Soraya (Jurnal Padamu Negeri, 2025)
The role of teachers in curriculum development extends beyond the planning stage and plays a crucial part in its implementation. This article aims to analyze and gain an in-depth understanding of teachers' roles as implementers in educational curriculum development. The discussion focuses on four key aspects: teachers as curriculum implementers in the classroom, providers of feedback, agents of change, and the challenges they face along with strategies to strengthen their roles. This study employs a qualitative approach using a literature review method by examining relevant sources. In classroom practice, teachers actively adapt and apply curriculum content to meet students' needs. As feedback providers, they offer valuable insights to stakeholders regarding curriculum effectiveness and areas for improvement. Additionally, teachers serve as agents of change by driving innovation and renewal in teaching practices. However, they also encounter various internal and external challenges that make their role increasingly complex. This article emphasizes the importance of recognizing and empowering teachers at every stage of curriculum development to establish a responsive and sustainable education system.